Effects of High-Intensity Interval Training on Cardiovascular Function and Risk Factors, Functional Impairments, and the Quality of Life in Coronary Artery Disease Patients: A Narrative Review - Nazir, Arnengsih; Biben, Vitriana; Gunanegara, Aggi; Clementius, Brandon (The Indonesian Heart Association, 2024)
Background: Coronary artery disease (CAD) causes damage to the cardiovascular system that leads to functional and quality of life (QoL) deterrence. Cardiac rehabilitation (CR) aims to improve cardiorespiratory fitness (CRF) to prevent disease progression and its risk factors. Aerobic exercise (AE) causes different physiological effects depending on the applied intensity. High-intensity interval training (HIIT) is being developed because of better effectivity than moderate-intensity continuous training (MICT). Even so, HIIT has not been prescribed generally. This review aimed to describe the effects of HIIT on cardiovascular function and risk factors, functional impairments, and the QoL. Methods: Articles were searched using PubMed and CINAHL databases with the keywords “high-intensity interval training”, “cardiac rehabilitation”, “exercise-based cardiac rehabilitation”, and “coronary artery disease”. Results: Twenty-two articles were found and used to explain sub-topics. Discussion: HIIT improves ventricular function, LVEF, heart contractility, and endothelial function which further improve systolic and diastolic blood pressure. Improvement in cardiovascular risk factors was better in HIIT compared to AE in lower intensities. Studies recommend HIIT for CAD patients due to significant cardiovascular adaptation in this exercise. Compared to MICT, most studies found that HIIT is better at improving CRF. HIIT also positively affects cognitive and affective functions. Research on the impact of HIIT on functional activity and QoL is still limited. However, one study found no differences in physical activity level and QoL in groups given HIIT or MICT. Conclusion: In CAD patients, HIIT is considered an alternative exercise that is more time-efficient than continuous exercise.